South Park and social research: What cartoons can tell us about sustainable mobility. Issue 2 (1st October 2014) - Newman, Daniel
This article discusses a topic that has previously been the domain of business studies: sustainable mobility and, in particular, consumer attitudes to electric vehicles. In conducting a social research study into electric vehicle drivers, I was presented with a finding that was not properly accounted for in the extant literature. At a loss, my chief reference point became a television show: South Park (1997–). This incident is used to acknowledge that academic fields such as business studies would be improved by exhibiting greater openness to other disciplines, such as cultural studies. In the spirit of breaking down this barrier, the article highlights something of the knowledge that can be gained from even the most cursory glance out at popular culture from within the closed world of business studies.